1994
DOI: 10.1002/jbm.820280115
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and XPS studies of titanium for biomaterial applications with respect to the effect of hydrogen peroxide

Abstract: Electrochemical measurements, x-ray photoelectron spectroscopy, and scanning tunneling microscopy have been used to study the effect of hydrogen peroxide on the passivity of titanium in a phosphate-buffered saline (PBS) solution. The results indicate that the passive film formed in the PBS solution--with and without addition of H2O2--may be described with a two-layer structure model. The inner layer has a structure close to TiO2 whereas the outer layer consists of hydroxylated compounds. The introduction of H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
99
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 33 publications
16
99
0
3
Order By: Relevance
“…Pan et al [11] investigated the electrochemical behaviour of commercially pure titanium in phosphate-buffered saline with and without H 2 O 2 additions. Gonzalez and Mirza-Rosca [12] investigated the electroche mical behaviour of titanium and several of its alloys in Ringer's solution using the electrochemical impedance spectroscopy.…”
Section: I In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
“…Pan et al [11] investigated the electrochemical behaviour of commercially pure titanium in phosphate-buffered saline with and without H 2 O 2 additions. Gonzalez and Mirza-Rosca [12] investigated the electroche mical behaviour of titanium and several of its alloys in Ringer's solution using the electrochemical impedance spectroscopy.…”
Section: I In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
“…Some studies using a surface reaction model have suggested that a titanium-peroxide complex is formed due to interaction with hydrogen peroxide when titanium is implanted in the human body [7][8][9] . Furthermore, the titanium surface was oxidized and dissolved by peroxide produced by bacteria and leukocytes during inflammatory reactions [10][11][12][13][14] . Similarly, in vitro studies have reported a decrease in resistance to corrosion and signs of pitting corrosion in titanium in the presence of hydrogen peroxide 6,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The influence of radiolysis on solution chemistry can be simulated by H202 additions [91,92,135,136]. Such additions lead to an increase in corrosion potential [137] and an improvement in stability of the film [91,92]. A dose rate of -lo4 ramour was shown to inhibit the propagation of crevice corrosion on the highly susceptible Ti Grade 2 [96].…”
Section: Influence Of Fluoride On Corrosion Of Titanium Allovs R971mentioning
confidence: 99%